Republic of Moldova : Second Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report, 2014)
This paper presents Second Post-Program Monitoring Discussions focusing on Moldova. Governance in the banking system remains poor and the condition of some large banks is fragile. The budget faces a tight financing situation, and-without corrective measures-the deficit is projected to widen significantly in 2015. Russia's new restrictions on imports from Moldova are exacerbating the ongoing slowdown in activity, easing inflationary pressures, and weakening export performance. Discussions mainly focused on policies to address the significant risks in the banking sector, return to a path of fiscal consolidation, and boost potential growth and preserve external stability.